Green Industry as a Tourism-Based MSME Development Strategy in Supporting a Sustainable Future (Case Study in Cowindo Sendang District, Tulungagung District, East Java) - Rahma Sandhi Prahara; M. Vicko Ardine Billie Kurnawan; Fayyadh Faza Muhammad; M. Vicko Alghozali Syahrial (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
Indonesia’s efforts to contribute as a member of the G20 are to maximize domestic economic development. One of the important problems faced in economic development is between meeting development needs and efforts to maintain aspects of environmental sustainability. Environmental problems are a contemporary issue that does not only occur at the macro level. However, at a micro level, the world is trying to get to know the issues of environmentally friendly products or what is known as Green Business or Green Industry. The impact of the existence of the green industry is that the global market trend is increasingly moving towards environmentally friendly products (eco-products). This condition is an obstacle and opportunity that needs to be immediately anticipated and utilized. For this reason, the government created a policy to help MSMEs through the Center for the Study of Green Industry and the Environment of the Ministry of Industry (2011), namely by developing environmentally friendly industries or green industries that can produce green products. MSMEs from the tourism sector in Tulungagung, East Java are Cowindo. Cowindo is one of the educational tours in Sendang District, Tulungagung Regency, East Java. Starting from local wisdom, it became known as a quality milk-producing area, then educational tourism was opened in 2018 and a sustainable production process was officially developed in 2020. In supporting sustainability at the domestic level, biogas is one of the strategies to make it happen. Apart from that, there are several implementations carried out by Cowindo as a form of green business, namely Bio-Slurry, the use of banana leaves as an alternative to reducing the use of soap and water, as well as processing lemongrass distillate for cows to drink as additional nutrition for the cows.